Ibn Taymiyya's Conception of Jihad: Corpus, General Aspects, and Research Perspectives - Mehdi Berriah (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
The question of jihad is fundamental to Ibn Taymiyya since he is one of the theologians of the Mamluk periodâ€”and probably of the entire medieval periodâ€”who wrote the most on this subject. Jihad was an essential part of the life of the famous theologian of Damascus, who took part in the Mamluk war effort as a volunteer in various expeditions. Over the last decades, scholars have been interested in the issue of jihad in Ibn Taymiyya and have highlighted several elements. These works have helped us learn more about the ideology of jihad in Ibn Taymiyya. However, it should be noted that those works focus on the jihad against a particular enemy (Mongols, heretics of the KisrawÄn, Shiâ€˜ites) in a particular context and do not deal much with Ibn Taymiyyaâ€™s general conception of jihad, for which several grey areas remain. This article will discuss Ibn Taymiyya and his general conception of jihad. My method is broken down into two steps to provide new elements and research perspectives. In the first instance, I will identify the maximum of Ibn Taymiyyaâ€™s writings and passages related to jihad, making the beginning of a type of inventory. Then I will analyze their content and cross-check them to bring to light general aspects of Ibn Taymiyyaâ€™s conception of jihad.